Genetic variability estimates in induced population of sesame (Sesamum indicum) - BEGUM, T; DASGUPTA, T (The Indian Journal of Agricultural Sciences, 2014)
An investigation was carried out to study the nature and magnitude of induced genetic variability in sesame (Sesamum indicum L.). Seeds of three sesame genotypes, Rama, SI 1666 and IC 21706 were treated with three doses of g-rays (200 Gy, 400 Gy and 600 Gy) and four concentrations of ethyl methane sulphonate (0.5%, 1.0%, 1.5% and 2.0%), separately. Mutant generations from M1 to M2 were raised to study the extent of variability, heritability and genetic advance in mutant populations. Mutations surpassed the magnitude of variability over control population in both the generations. Genotypic and phenotypic variances were higher for sterility% and 1000-seed weight in both M1 and M2 generations. With regardless of the genotype, M1 generation professed maximum genotypic and phenotypic coefficients of variability (GCV and PCV) for number of seeds per capsule. On the contrary, in M2 generation induced populations of all the three genotypes engendered maximum GCV and PCV for seed yield per plant. High heritability for sterility percentage and 1000-seed weight coupled with high genetic advance inferred that additive gene effects were important in determining these characters and could be improved through mass selection.